Water Deficit-Responsive QTLs for Cell Wall Degradability and Composition in Maize at Silage Stage - Virlouvet, Laëtitia; El Hage, Fadi; Griveau, Yves; Jacquemot, Marie-Pierre; Gineau, Emilie; Baldy, Aurélie; Legay, Sylvain; Horlow, Christine; Combes, Valérie; Bauland, Cyril; Palafre, Carine; Falque, Matthieu; et al. (Frontiers in Plant Science, 2019)
Lignocellulosic biomass degradability is of upmost interest to estimate biomass valorization in the context of animal feeding and biorefinery. Moreover, in the actual context of climate variation, biomass is being produced under constrained irrigation conditions. Although the negative impact of water deficit on biomass yield has often been mentioned, its impact on biomass quality has only been recently reported in different species. In the present study, we combined the mapping power of a maize recombinant inbred line population with robust near infrared spectroscopy predictive equations to track the response to water deficit of traits associated to biomass quality. The population was cultivated under two contrasted water regimes over three consecutive years in the south of France and harvested at silage stage. We showed that cell wall degradability and O4-linked H lignin subunits were increased in response to water deficit, while lignin and p-coumaric acid contents were reduced. A mixed linear model was fitted to map quantitative trait loci (QTLs) for agronomical and cell wall related traits. These QTLs were categorized as ‘constitutive’ (QTL with an effect whatever the irrigation condition) or ‘responsive’ (QTL involved in the response to water deficit) QTLs. Fifteen clusters of QTLs encompassed more than two third of the 213 constitutive QTLs and 13 clusters encompassed more than 60% of the 149 responsive QTLs. Interestingly, we showed that only half of the responsive QTLs co-located with constitutive and yield QTLs, suggesting that specific genetic factors support biomass quality response to water deficit. Overall, our results demonstrate that water deficit favors cell wall degradability and that breeding effort to select for resilient lines can be achieved without reducing plant performance.